2021
DOI: 10.3844/ajbbsp.2021.478.489
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of Corn Steep Liquor to Biofertilizer by Symbiotic Fermentation

Abstract: Corn Steep Liquor (CSL) is wastewater from corn starch industry. The huge amount generation made it as a serious environmental problem. But CSL is nutrient-rich with diverse amino acids and other trace elements. In this study, symbiotic biofertilizer was studied using CSL as main substrate. In this study, 9 industrial strains, which were recognized as high performance species in the biofertilizer industry were collected, including four bacillus, four fungus and one yeast species. Three dominant strains were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Thus, it has been observed that the application of biostimulant products with CSL are able to regenerate the state of the soils, shown as notable changes in the physicochemical conditions of the treated soil and the essential nutrients such as phosphorus, nitrogen, and potassium. CSL promotes the growth of bacteria that fix nitrogen and solubilize phosphorus [45]. At the same time, this byproduct acts as a biocontrol agent for the pathogens B. subtilis and Pseudomonas sp.…”
Section: Improvement Of Soil Healthmentioning
confidence: 99%
“…Thus, it has been observed that the application of biostimulant products with CSL are able to regenerate the state of the soils, shown as notable changes in the physicochemical conditions of the treated soil and the essential nutrients such as phosphorus, nitrogen, and potassium. CSL promotes the growth of bacteria that fix nitrogen and solubilize phosphorus [45]. At the same time, this byproduct acts as a biocontrol agent for the pathogens B. subtilis and Pseudomonas sp.…”
Section: Improvement Of Soil Healthmentioning
confidence: 99%